2018
DOI: 10.1002/ijfe.1659
|View full text |Cite
|
Sign up to set email alerts
|

Investor trading behaviour and stock price crash risk

Abstract: This paper sheds new light on the relation between investor trading behaviour and crash risk to examine how investors react to stocks with lottery features in Chinese Stock Market. We find that investor trading behaviour has a greater impact on stocks with higher crash risk, which implies that investors overreact to stocks with higher stock price crash risk. Furthermore, investor trading behaviour has strongest effects on stocks with highest crash risk and highest idiosyncratic risk and has weakest effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…For example, many studies have focused on firm-level internal factors such as corporate tax avoidance [1], opaque financial reports [2,3], accounting conservatism [4], corporate social responsibility [5], CEO overconfidence [6]), financial constraints [7], stock liquidity [8], corporate financing [9], corporate debt maturity [10], stock ownership [11], equity incentives [12], corporate governance [13], and other cases. However, several other studies on factors such as religion [14,15], social trust [16], media sentiment and mawkishness [17], individualism [18], Sustainability 2021, 13, 3688 2 of 16 political connections [19], trading behavior and sentiment of investors [20,21], and product market competition [22] have tried to investigate a couple of these corporate external factors. This study has a slightly different approach and aims to examine simultaneously the effects of some corporate characteristics as well as the most important macroeconomic external factors on the stock price crash.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many studies have focused on firm-level internal factors such as corporate tax avoidance [1], opaque financial reports [2,3], accounting conservatism [4], corporate social responsibility [5], CEO overconfidence [6]), financial constraints [7], stock liquidity [8], corporate financing [9], corporate debt maturity [10], stock ownership [11], equity incentives [12], corporate governance [13], and other cases. However, several other studies on factors such as religion [14,15], social trust [16], media sentiment and mawkishness [17], individualism [18], Sustainability 2021, 13, 3688 2 of 16 political connections [19], trading behavior and sentiment of investors [20,21], and product market competition [22] have tried to investigate a couple of these corporate external factors. This study has a slightly different approach and aims to examine simultaneously the effects of some corporate characteristics as well as the most important macroeconomic external factors on the stock price crash.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above-mentioned biases, other biases such as hindsight, loss aversion, self-control, endowment, self-attribution, ambiguity aversion, and others are distinguished. Other authors (Tekce et al, 2016;Ye et al, 2020;L. Zhou & Huang, 2019) mention other deviations in investor behavior in financial markets in addition to the biases listed above.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been found that individuals are influenced by preconceived notions, stereotypes, various perceptual illusions, information processing errors and emotions when making investment decisions. Clearly, these facts are inconsistent with rational behavior, which is based on classical models, and therefore the science of behavioral finance emphasizes such key features of irrational behavior that characterize the modern investors (Barber & Odean, 2013;Ryu et al, 2017;L. Zhou & Huang, 2019):…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jia and Yang (2017) use the total market buyer‐initiated volume and the total market seller‐initiated volume data to construct the disagreement of crowded trades index. Zhou and Huang (2019) use the buy‐sell imbalance to represent the investor trading behaviour. If retail investors are net buyers of a given stock over a given time period, then the buy‐sell imbalance is positive.…”
Section: Individual Stock Investor Sentimentmentioning
confidence: 99%